Explainable Deepfake video detection using Convolutional Neural Network and CapsuleNet - Ishrak, Gazi Hasin; Mahmud, Zalish; Farabe, Md. Zami Al Zunaed; Tinni, Tahera Khanom (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.